Contribution degree of fluidity control for polymer flooding in heavy oil reservoir. Issue 4 (February 2019) - Shi, Leiting; Zhu, Shijie; Cao, Jie; Zhao, Wensen; Shu, Zheng; Ye, Zhongbin
Abstract: The unfavorable mobility ratio of heavy oil reservoirs makes the effect of polymer flooding poor. From the mechanism of polymer mobility control, the contribution of viscosity and residual resistance factor to the effect of oil displacement is analyzed to find the development direction of polymer flooding suitable for heavy oil reservoir. Firstly, the mathematical model of polymer flooding can be established to characterize the solution viscosity and residual resistance factor, and then the numerical solution is obtained. The corresponding contribution degree is analyzed by MATLAB using the grey correlation method. The results show that the contribution of the viscosity of the polymer solution to the injection pressure (75%) is significantly higher than the residual resistance factor (25%), but the contribution to the recovery (48%) is slightly lower than the residual resistance factor (52%). Under the conditions of limited injection pressure, the oil displacement system with low viscosity and high residual resistance factor is more beneficial to the mobility control of polymer flooding in heavy oil reservoirs.